1999
DOI: 10.1530/jrf.0.1150111
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian antral follicular dynamics and their relationships with endocrine variables throughout the oestrous cycle in breeds of sheep differing in prolificacy

Abstract: Transrectal ultrasonography of ovaries was performed each day in non-prolific Western white-faced (n = 12) and prolific Finn ewes (n = 7), during one oestrous cycle in the middle portion of the breeding season (October-December), to record the number and size of all follicles > or = 3 mm in diameter. Blood samples collected once a day were analysed by radioimmunoassay for concentrations of LH, FSH and oestradiol. A cycle-detection computer program was used to identify transient increases in concentrations of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
157
4
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(189 citation statements)
references
References 33 publications
24
157
4
4
Order By: Relevance
“…Similar results have been reported in cattle (McCaughey and Patterson 1981), ewes (Bartlewski et al 1999), and buffaloes (Gupta and Purohit 2001). On the other hand, in our study and…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results have been reported in cattle (McCaughey and Patterson 1981), ewes (Bartlewski et al 1999), and buffaloes (Gupta and Purohit 2001). On the other hand, in our study and…”
Section: Discussionsupporting
confidence: 93%
“…This difference in oestradiol-17β concentrations could be related to the fact that administration of sponges for 14 days was more effective with respect to oestrus detection and pregnancy rate. It has been suggested that the diameter of ovarian follicles is a very important factor for successful ovulation (Kohno et al 2005); furthermore, the largest antral follicles are the main source of oestradiol and there are periods of increased oestradiol secretion throughout the oestrous cycle in ewes (Bartlewski et al 1999;Duggavathi et al 2006). The higher oestradiol-17β concentrations at oestrus, when sponges remain in situ for 12 days may be related to the late ovulation and lower pregnancy rate in this group, since follicle diameters could be linked with oestradiol-17β concentrations and pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that short-term protocols with progesterone, eCG and prostaglandin are sufficient to induce estrus and ovulation in ewes. The average number of ovulations we verified (1.5±0.6) are similar to those reported in Western White Face ewes (Bartlewski et al, 1999). The largest follicle diameters obtained is in accordance to Ginther et al (1995), Bartlewski et al (1999) and Evans (2003), who reported that ewe's preovulatory follicles reach maximum diameter of 5 to 7 mm.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the use of intravaginal progesterone devices up to three times did not affect (P>0.05) the rate of ovulating animals (a total of 88.9%, 24/27), similar to the 90% also obtained in Santa Inês ewes receiving a shortterm treatment with progestagen (Cavalcanti et al, 2006). These data indicate that short-term protocols with progesterone, eCG and prostaglandin are sufficient to induce estrus and ovulation in ewes.…”
Section: Discussionsupporting
confidence: 80%